2007
DOI: 10.1159/000110421
|View full text |Cite
|
Sign up to set email alerts
|

Abducens Nerve Pareses Associated with Aneurysmal Subarachnoid Hemorrhage

Abstract: Background: This study was performed to reveal the incidence and the etiology of abducens nerve pareses associated with aneurysmal subarachnoid hemorrhage. Methods: At the time of admission, CT scan was carried out, and the thickness of the prepontine subarachnoid clot was measured. Results: In total 101 patients met the study requirements and abducens nerve pareses was apparent in 6 patients (5.9%). There were significant differences between the group with abducens nerve pareses and the group without in regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
0
18
1
Order By: Relevance
“…The authors found the size of the prepontine clot to be the best predictor of the presence of palsy [8]. This argues for a primarily mechanical effect.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found the size of the prepontine clot to be the best predictor of the presence of palsy [8]. This argues for a primarily mechanical effect.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 6% (Munakata et al 2007) are associated with sixth nerve palsy and Edgar et al (1992) speculated that direct shock to the brain stem caused by aneurysmal rupture and stretching of structures lying between the brain and the skull in the subarachnoid space were the factors causing abducens nerve pareses. Localised compression of the nerve by a primary pituitary tumour, craniopharyngioma or meningioma in the base of the skull or close to the pituitary fossa or cavernous sinus.…”
Section: Peripheral Damagementioning
confidence: 99%
“…It has been reported that vascular causes account for 20% of CN3 palsies, for 18.6% of CN4 palsies and for 17.7% of CN6 palsies [6]. Other etiologies such as aneurysm, trauma, neoplasm, brain stem infarction, infection, inflammation, sinus thrombosis and multiple sclerosis have also been proposed [7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%